2015
DOI: 10.5935/1678-9741.20150040
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postoperative atrial fibrillation in patients undergoing on-pump and off-pump coronary artery bypass grafting

Abstract: ObjectiveTo determine the incidence of postoperative atrial fibrillation in patients undergoing on-pump and off-pump coronary artery bypass grafting.MethodsA retrospective study with analysis of 230 medical records between January 2011 and October 2013 was conducted.ResultsFifty-six (24.3%) out of the 230 patients were female. The average age of patients undergoing on-pump coronary artery bypass grafting was 59.91±8.62 years old, and off-pump was 57.16±9.01 years old (P=0.0213). The average EuroSCORE for the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 22 publications
3
29
2
3
Order By: Relevance
“…(2-4,12) The mean age of patients who developed POAF was significantly higher than in patients who had arrhythmia. The anatomical and functional changes related to ageing and worsening of clinical conditions can contribute for this finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2-4,12) The mean age of patients who developed POAF was significantly higher than in patients who had arrhythmia. The anatomical and functional changes related to ageing and worsening of clinical conditions can contribute for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…(8) In relation to use of ECC, researchers concluded that CABG without ECC did not reduce the incidence of POAF. (4) Measures that reflect intraoperative time of ischemic heart, such as aortic clamp time, have been reported as risk factors for POAF, although literature still controversial on the subject. (3,20) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,[11][12][13][14][15][16][17][18] Still, a few authors report PAOF frequencies lower than 15%. 4,10,15,19,20 According to most of the available literature, the use of cardiopulmonary bypass does not impact PAOF occurrence Abbreviations: AF, atrial fibrillation; DB, diagonal branch; DM, diabetes mellitus; COPD, chronic obstructive pulmonary disease; CI, confidence interval; CRF, chronic renal failure; LADA, left anterior descending artery; LMA, left marginal artery; OR, odds ratio; RCA, right coronary artery; SAH, systemic arterial hypertension. and the off-pump approach cannot be considered a protective factor for PAOF in patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 99%
“…General factors include older age, male gender, obesity, preexisting congestive heart failure, chronic renal failure, or COPD which are all risk factors for POAF [911]. Identification of patients who are at higher risk of POAF using genetic markers might be an important step for prevention of this type of operative complication and may provide important insight into the pathogenesis of atrial fibrillation (AF) and new therapeutic strategies for individual patients according to relative risk [12, 13]. …”
Section: Introductionmentioning
confidence: 99%